Colchicine: Repositioning an “ancient” medicine in the 21st century - E. L. Nasonov; O. M. Drapkina (Научно-практическая ревматология, 2024)
The main indications for colchicine treatment until recently were gout, pericarditis, familial Mediterranean fever and some other auto-inflammatory diseases. The expansion of indications (repositioning) for the use of colchicine in the direction of prevention of cardiovascular complications should be considered as one of the major events in medicine of the XXI century. Deciphering the role of inflammation as the most important mechanism for the development of atherosclerosis has created prerequisites for the development of the concept of anti-inflammatory therapy of atherosclerosis, in which low-dose colchicine therapy can take an important place, complementing the effects of aspirin, statins and antihypertensive therapy. The analysis of materials from randomized placebo-controlled studies of colchicine indicates a decrease in the frequency of cardiovascular complications in patients with coronary heart disease (by 31%) and in patients who have recently suffered a myocardial infarction (by 23%), as well as myocardial infarction (by 33%), stroke, the need for myocardial revascularization and cardiovascular mortality. The use of colchicine in a low dose (0.5 mg/day) is approved by the U.S. Food and Drug Administration for the prevention of cardiovascular complications in patients with coronary heart disease. It can be assumed that in the future colchicine will take an important place in the prevention and treatment of cardiovascular pathology associated with atherosclerotic vascular disease.